BEHAVIORAL ECONOMICS AND BEHAVIORAL FINANCE IN DECISION MAKING - Oktaviana, Ulfi Kartika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Behavioral economics emphasizes the importance of empirical evidence and facts that contradict traditional economic assumptions. Several empirical studies have shown that individuals are prone to systematic bias in decision-making, as they do not always make decisions that are in their best interest. Behavioral Economics and Behavioral Finance aim to incorporate psychological aspects into the decision-making process, although it focuses on financial decisions and financial markets. This paper aims to describe the concept of economic behavior and its relation to financial behavior in decision-making using a literature survey. Behavioral economics and behavioral finance involve the science of psychology to study economics and finance, explaining that human biases can influence people's financial decision-making. This paper examines some of the behavioral biases that usually occur in investor decision-making, such as heuristics, overconfidence, mental accounting, and loss aversion, etc. and each of them shows their own representation and the way they influence decision-making